101 facts about parakeets - Barnes, Julia, 1955- (Milwaukee, WI : Gareth Stevens Pub., 2002)
Describes the history, physical characteristics, and behavior of parakeets, and presents information on choosing, training, and caring for one as a pet.
Includes bibliographical references (p. 31) and index.
Keywords: Budgerigar -- Miscellanea -- Juvenile literature; Parakeets; Pets